Pengaruh 2,4-D dan BAP terhadap Multiplikasi Tanaman Vanili (Vanilla planifolia Andrews): Pengaruh 2,4-D dan BAP terhadap Multiplikasi Tanaman Vanili (Vanilla planifolia Andrews) - Restanto, Didik Pudji; Nadiya, Nisma Riyadh; Dewanti, Parawita; Khozin, Mohammad Nur; Prayoga, Mohammad Candra (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Vanilla is a plant that has many benefits, high selling value and potential to be developed. Conventional propagation of vanilla such as through cuttings has not been effective, so a more effective method of propagation is needed, one of which is propagation through tissue culture. In-vitro propagation of vanilla can be through shoot multiplication to produce fast plantlets. One of the successes of shoot multiplication is influenced by the hormone given. This study aims to determine the effect of giving a combination of 2,4-D and BAP on the multiplication of vanilla shoots. The study design used CRD with a combination factor of 2,4-D (concentration 0.5 mg/L, 1.0 mg/L, and 1.5 mg/L) and BAP (concentration 0.25 mg/L, 0.5 mg/L, and 0.75 mg/L). The explants used were vanilla stem segments. Based on the research results, the combined treatment with concentrations of 2,4-D 1 mg/L and BAP 0.5 mg/L had a very significant effect on the multiplication of vanilla shoots with the fastest emergence of shoots with an average of 6.6 wap, the highest number of shoots was 7 shoots, and the survival percentage was 100%.